PENERAPAN METODE MATEMATIKA REALISTIK DALAM MENINGKATKAN HASIL BELAJAR SISWA DI SEKOLAH DASAR - Irma Yunita Sari; Regita Dewi Wulandari; Fitria Ainun Nazla; Nabilah Nur Azmi; Imron Fauzi (Jurnal Pendidikan Dasar dan Keguruan, 2022)
From empirical facts, it is stated that the majority of students in Indonesia do not like mathematics. This is based on literature studies from various journals that new methods for understanding mathematics continue to be developed to improve the quality of education in Indonesia, one of which is the application of realistic mathematical methods. The research method used is qualitative by accumulating various literature studies to obtain comprehensive data. In general, understanding mathematics is only based on memorizing formulas and practicing questions. This is different from the concept of applying realistic mathematical methods which will quickly build understanding of mathematics lessons. The systematic application of realistic mathematical methods will then be discussed in this paper.